2020
DOI: 10.1177/2516608520974512
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Therapy in Stroke Rehabilitation: Why, How Early, and Effects: A Meta-analysis

Abstract: Background and Aims: The use of visual stimuli to facilitate a desired response in the affected limb in mirror therapy (MT) makes it an effective treatment modality even in instances of a complete plegic upper extremity poststroke. This article analyzes the effects of MT on impairments, activity limitation, and participation restriction in the acute and chronic phases poststroke. Methods: In total, 16 out of 3871 studies were included in the meta-analysis, using PRISMA guidelines. Data were categorized based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The articles included in this study were published in Chinese and English. Among them, 16 articles were journal articles 9–12,14–25 . All original studies were RCTs 13 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The articles included in this study were published in Chinese and English. Among them, 16 articles were journal articles 9–12,14–25 . All original studies were RCTs 13 .…”
Section: Resultsmentioning
confidence: 99%
“…The interventions provided to the experimental group were mirror visual feedback therapy alone or combined with conventional rehabilitation therapy, while the interventions provided to the control group were conventional rehabilitation therapy or sham mirror therapy. Eleven articles 11–14,16,18–20,22,24,25 assessed the methodological quality of RCTs by applying the Cochrane Handbook Systematic Evaluation Tool, four by applying the PEDro scale, 9,10,21,23 one study 17 applied the modified Jadad scale, while one study 15 applied the Physiotherapy Evidence Database scale. The basic characteristics of the included studies are shown in Table 1 (the complete Table 1 is in Supplemental Digital Content 2, http://links.lww.com/PHM/B748).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations